2022
DOI: 10.1021/acs.langmuir.2c00230
|View full text |Cite
|
Sign up to set email alerts
|

Topological Dynamics of Micelles Formed by Geometrically Varied Surfactants

Abstract: The molecular architecture of sugar-based surfactants strongly affects their self-assembled structure, i.e., the type of micelles they form, which in turn controls both the dynamics and rheological properties of the system. Here, we report the segmental and mesoscopic structure and dynamics of a series of C16 maltosides with differences in the anomeric configuration and degree of tail unsaturation. Neutron spin-echo measurements showed that the segmental dynamics can be modeled as a one-dimensional array of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Beyond this point, no significant changes in η 0 were observed (Figure 6A). Simultaneously, it should be noted that shearthinning 40,42 ceased when the pH dropped below 2.3 (Figure S11B). The cryo-TEM result further confirmed that the PCB-AzoNa WLMs had been destroyed completely at pH 2.0 (Figure 6B).…”
Section: Fabrication and Characteristics Of Pcb-azona Wlmsmentioning
confidence: 85%
See 3 more Smart Citations
“…Beyond this point, no significant changes in η 0 were observed (Figure 6A). Simultaneously, it should be noted that shearthinning 40,42 ceased when the pH dropped below 2.3 (Figure S11B). The cryo-TEM result further confirmed that the PCB-AzoNa WLMs had been destroyed completely at pH 2.0 (Figure 6B).…”
Section: Fabrication and Characteristics Of Pcb-azona Wlmsmentioning
confidence: 85%
“…Besides, a typical shear-thinning phenomenon was observed in the plot of shear rate (s −1 ) versus steady-state viscosity (η, mPa•s) for the PCB-AzoNa system (Figure S4), giving another strong signal of the formation of WLMs. 40,42 The zero-shear viscosities (η 0 , mPa•s) were obtained by extrapolating the viscosity plot (Figure S4) along the plateau to zero-shear rate. Then, the appropriate molar ratio of AzoNa to PCB (n AzoNa /n PCB ) was determined from the dependence of η 0 on n AzoNa /n PCB (Figure 1B).…”
Section: Fabrication and Characteristics Of Pcb-azona Wlmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydraulic fracturing technology has greatly stimulated the productivity of oil-gas wells in low-permeability formations for several decades. In recent years, polymer-based fracturing fluids have dominated the fracturing industry due to their excellent fracturing performance. A major issue with these fluids is the formation damage, inhibiting their ability to improve production efficiency. , The eco-friendly viscoelastic surfactant (VES) fracturing fluid, which comprises highly entangled wormlike micelles (WLMs), is an ideal candidate to replace the traditional fracturing fluid.…”
Section: Introductionmentioning
confidence: 99%